Green Collaboration: Agriculture and Fisheries Cultivation in Realizing Food Security - Fazira, Nurul; Fajriani , Annisa (Professorline, 2024)
Food security is an increasingly important global issue amidst population growth and climate change. This article examines the potential for collaboration between the agricultural and aquaculture sectors in realizing sustainable food security. This